A systematic observation method for evaluating the effectiveness of defensive actions in volleyball - Hilchenko, A.D. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the factors influencing the effectiveness of the defensive actions of volleyball among students and to develop recommendations for optimizing the training process. Methods and structure of the study. The sample consisted of 60 second-year Volleyball students (30 males and 30 females) aged 19-21 years. The following methods were used in the course of the study: systematic structured observation, video analysis using Dartfish software, and pedagogical testing. Results and conclusions. The effectiveness of the actions of volleyball students in defense is determined by the level of development of physical, technical and tactical readiness, gender, as well as individual psychological characteristics. The most common errors were identified: incorrect starting position, premature/late movement, mismatch of ball reception technique and incorrect position selection when blocking.